The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ane.13487
|View full text |Cite
|
Sign up to set email alerts
|

Basal IL‐6 and S100b levels are associated with infarct volume

Abstract: Objectives The study of biomarkers related to the infarct volume of acute ischaemic stroke (AIS) is a valuable clinical strategy. We conducted a prospective study to evaluate the relationship between a wide panel of biomarkers involved in different biochemical pathways and lesion volume. Materials & Methods We studied 332 patients with AIS. Infarct volume was calculated from diffusion weighted imaging (DWI). Blood samples were drawn within 24 h of symptom onset to test a panel of biomarkers that included high‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We did not assess S100b levels in serum in this study. S100b serum levels are known to be higher in stroke cases with larger lesion volumes ( 65 , 66 ). It would be of interest to assess if clot S100b content reflects serum levels in future work.…”
Section: Discussionmentioning
confidence: 99%
“…We did not assess S100b levels in serum in this study. S100b serum levels are known to be higher in stroke cases with larger lesion volumes ( 65 , 66 ). It would be of interest to assess if clot S100b content reflects serum levels in future work.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated a good correlation with infarct volume within the first week after AIS 127 . Purroy et al 128 combined NfL levels at 48 h with NIHSS at 24 h and improved the prediction of poor outcomes (mRS: 3 months ≥ 3). Chen et al 129 showed that higher NfL levels before, immediately after, and 24 h after MT were associated with unfavourable outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…IL‐6 is an inflammatory cytokine with a wide variety of biological functions and has been independently associated with infarct volume 24 h after symptom onset in a study with 332 IS patients. Higher IL‐6 levels might also be related to higher rates of unsuccessful recanalization due to an imbalance toward a proinflammatory and procoagulant state 128,137 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In human studies, the serum level of IL-6 is significantly correlated with infarct size and survival in stroke [ 14 , 15 ]. Francisco et al [ 16 ] demonstrated that IL-6 emerged as the only biomarker independently associated with infarct volume in AIS patients. Similarly, in our study, the levels of IL-6 were increased in AIS patients with NIHSS scores greater than 5.…”
Section: Discussionmentioning
confidence: 99%